2019
DOI: 10.1038/s41598-019-50861-2
|View full text |Cite
|
Sign up to set email alerts
|

Radio-enhancement effects by radiolabeled nanoparticles

Abstract: In cancer radiation therapy, dose enhancement by nanoparticles has to date been investigated only for external beam radiotherapy (EBRT). Here, we report on an in silico study of nanoparticle-enhanced radiation damage in the context of internal radionuclide therapy. We demonstrate the proof-of-principle that clinically relevant radiotherapeutic isotopes (i.e. 213Bi, 223Ra, 90Y, 177Lu, 67Cu, 64Cu and 89Zr) labeled to clinically relevant superparamagnetic iron oxide nanoparticles results in enhanced radiation dam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 79 publications
1
20
0
Order By: Relevance
“…The greatest difference in SSBs and DBSs for the emission profiles occurred at 400 eV where β + demonstrated a 55% integral increase in SSBs compared to electrons, and a 117% increase in DSBs. These results are consistent with our previous study demonstrating the use of 89 Zr and 64 Cu for dose enhancement in nuclear medicine imaging compared to β − therapeutic isotopes such as 67 Cu, by virtue of their higher ionization properties 13 . Another in vivo study demonstrated that both 64 Cu (with 38.5% β − ) and 67 Cu (with 100% β − ) were an effective targeted β − RNT for subcutaneous human colon carcinoma carried in hamster thighs when radiolabeled with a mouse anti-human colorectal cancer 14 .…”
Section: Mainsupporting
confidence: 93%
“…The greatest difference in SSBs and DBSs for the emission profiles occurred at 400 eV where β + demonstrated a 55% integral increase in SSBs compared to electrons, and a 117% increase in DSBs. These results are consistent with our previous study demonstrating the use of 89 Zr and 64 Cu for dose enhancement in nuclear medicine imaging compared to β − therapeutic isotopes such as 67 Cu, by virtue of their higher ionization properties 13 . Another in vivo study demonstrated that both 64 Cu (with 38.5% β − ) and 67 Cu (with 100% β − ) were an effective targeted β − RNT for subcutaneous human colon carcinoma carried in hamster thighs when radiolabeled with a mouse anti-human colorectal cancer 14 .…”
Section: Mainsupporting
confidence: 93%
“…They demonstrated not only radio-enhancement for internal RT by use of NPs, but also the strongest interaction with 20 nm inter-NP distance. 77 One of the most crucial aims of the production of nanocarriers as drug carriers is to develop safer and more effective therapeutic and diagnostic modalities. 78 Imaging can be successfully used for the evaluation of biodistribution and pharmacokinetics of nanomedicine-based drug delivery systems.…”
Section: Drug Delivery Systemsmentioning
confidence: 99%
“…Thus, HIR-FH can also potentially offer a unique platform for targeted and selective internal radionuclide therapy, 78 while HIR-FH or in general any HIR radiometal-SPION can serve as metal-based radio-enhancer as we have recently reported. 79 With its simple chemical synthesis procedure, HIR can be potentially utilized in clinical settings without the possible complications of a chelate-based chemistry. 33-35,46,50 (5) While there currently exist both single- 72 or dual-modality 66 nanoparticle platforms, the chelatefree HIR method discussed in this work is also conducive to the development of multimodal imaging probes, allowing for new areas of research.…”
Section: Significance Of Chelate-free Hir Radiolabelingmentioning
confidence: 99%